Peran Posyandu Lansia dalam Meningkatkan Kesejahteraan Lansia di Kelurahan Sekaran Kecamatan Gunungpati - Prasetyo, Kiki Yudhi; Arifien, Moch; Indrayati, Ariyani (Jurusan Geografi, Fakultas Ilmu Sosial, Universitas Negeri Semarang, 2018)
Based on the results of the projection of the population based on age, one of which is the populationwith age, Central Java Province ranks the second largest number of elderly in Indonesia, amountingto 11.4%. Sekaran village is one sub-district located in Semarang City, precisely GunungpatiSubdistrict has a total of 206 people. The background above the researcher wants to s tudy further ina study entitled